Evaluasi Sistem Informasi Akuntansi Pembelian dan Persediaan Bahan Baku pada PT Sumber Bahagia Metalindo - Siti Elda Hiererra; Efrizon Efrizon; Yun Yun; Eka Yuliany (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The research objective was to evaluate, learn and analyze whether the company’s business processes in accounting information systems of purchases and inventory of raw materials implemented in the company run as expected; to find out whether the accounting information system of purchasing and inventory of raw materials is well integrated, and to provide recommendations and suggestions to improve the weaknesses in the system for the company’s assets can be well cared for. Several methodologies are implemented in this research, which are literature study, field study, such as: interviews, observation, checklists, and documentation review followed by data analysis. Audit is implemented using audit around the computer. The results obtained are in the form of data analysis presented as problem findings, the impacts and recommendations for remedial action. It can be concluded from the results of this study that PT. Sumber Bahagia Metalindo owns sufficient information system control, but still there are some weaknesses to be improved in order to improve control process to the better objective.